Representasi Nilai-Nilai Pesantren dalam Buku Ajar Bahasa Arab MI Melalui Semiotika Roland Barthes - Gunarti, Tri Tami; Ahmadi, Mubarok (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This study aims to reveal the representation of Islamic boarding school values ​​in the 2020 Islamic Elementary School (MI) Arabic language textbook published by the Indonesian Ministry of Religious Affairs, using Roland Barthes' semiotic approach. This textbook not only serves as a language learning medium, but also serves as an instrument for character building through narratives and illustrations rich in symbolic meaning. The method used is qualitative with visual and text analysis techniques, including interpretation of verbal and nonverbal signs (images, symbols, and illustrations) in the textbook. The results show that there are various representations of Islamic boarding school values ​​such as politeness, courtesy, discipline, and Islamic identity shown through symbols such as neat uniforms, peci (traditional cap), jilbab (headscarf), and interactions between students and teachers. These signs are analyzed through Barthes's three levels of meaning: denotative, connotative, and mythological, which ultimately lead to the construction of Islamic boarding school educational ideology in formal classrooms. These findings have important implications for the development of Arabic language textbooks that emphasize not only linguistic aspects but also serve as a medium for transmitting Islamic values ​​in a contextual and down-to-earth manner.